Step
*
of Lemma
real-vec-triangle-equality
∀n:ℕ. ∀x,y,z:ℝ^n.  ((r0 < d(y;z)) 
⇒ (d(x;z) = (d(x;y) + d(y;z))) 
⇒ (real-vec-be(n;x;y;z) ∧ ((r0 < d(x;y)) 
⇒ x-y-z)))
BY
{ ((UnivCD THENA Auto)
   THEN Unfold `real-vec-dist` -1
   THEN (Assert ||x - z|| = ||x - y + y - z|| BY
               (BLemma `real-vec-norm_functionality`
                THEN Auto
                THEN D 0
                THEN Auto
                THEN RepUR ``real-vec-sub real-vec-add`` 0
                THEN nRNorm 0
                THEN Auto))
   THEN (RWO  "-1" (-2) THENA Auto)
   THEN (FLemma `Minkowski-equality` [-2] THENA Auto)
   THEN ExRepD) }
1
1. n : ℕ
2. x : ℝ^n
3. y : ℝ^n
4. z : ℝ^n
5. r0 < d(y;z)
6. ||x - y + y - z|| = (||x - y|| + ||y - z||)
7. ||x - z|| = ||x - y + y - z||
8. t : ℝ
9. r0 ≤ t
10. req-vec(n;x - y;t*y - z)
11. (r0 < ||x - y||) 
⇒ (r0 < t)
⊢ real-vec-be(n;x;y;z) ∧ ((r0 < d(x;y)) 
⇒ x-y-z)
Latex:
Latex:
\mforall{}n:\mBbbN{}.  \mforall{}x,y,z:\mBbbR{}\^{}n.
    ((r0  <  d(y;z))
    {}\mRightarrow{}  (d(x;z)  =  (d(x;y)  +  d(y;z)))
    {}\mRightarrow{}  (real-vec-be(n;x;y;z)  \mwedge{}  ((r0  <  d(x;y))  {}\mRightarrow{}  x-y-z)))
By
Latex:
((UnivCD  THENA  Auto)
  THEN  Unfold  `real-vec-dist`  -1
  THEN  (Assert  ||x  -  z||  =  ||x  -  y  +  y  -  z||  BY
                          (BLemma  `real-vec-norm\_functionality`
                            THEN  Auto
                            THEN  D  0
                            THEN  Auto
                            THEN  RepUR  ``real-vec-sub  real-vec-add``  0
                            THEN  nRNorm  0
                            THEN  Auto))
  THEN  (RWO    "-1"  (-2)  THENA  Auto)
  THEN  (FLemma  `Minkowski-equality`  [-2]  THENA  Auto)
  THEN  ExRepD)
Home
Index